Storytelling in Optimizing the Learning of the History of Noah As - Raihana, Fildza Qonita; Tabroni, Imam; Maharjan, Kailie; Mark, Eladdadi (Journal Emerging Technologies in Education, 2023)
Background. As Muslims, we are obliged to study knowledge to be a provision in life, one of which is history. History is an event that happened in the past that we can learn and take lessons from for future life. Purpose. Derived from Arabic, syajarah, which means tree. Like a small seed that can grow as a big tree. History is considered to bring change, that's why history must be studied. Especially the history of the Prophets and Messengers. Method. . It is very important for children to learn in order to get the wisdom and advice contained therein. Results. Apart from gaining knowledge from formal education, non-formal education is also important for children. Non-formal education is present as a complement to formal education, namely to fulfill certain aspects that are not given in formal education. Conclusion. To fill the school void in certain aspects, it is good that parents can look for alternatives from non-formal education, one of which is by enrolling children in the Al-Qur'an Education Park. Taman Pendidikan Al-Qur'an or commonly abbreviated as TPA.